Cytotoxicity and biodistribution studies on PEGylated EDA and PEG cored PAMAM dendrimers. Issue 16 (1st November 2016) - Gürbüz, Mustafa U.; Öztürk, Kıvılcım; Ertürk, Ali S.; Yoyen-Ermis, Digdem; Esendagli, Gunes; Çalış, Sema; Tülü, Metin
Abstract: Starting from Ethylenediamine (EDA) or poly(ethylene glycol) tetra amine (4-arm-PEG) cores, two different peripheral methylester (–COOCH3 ) or amine (–NH2 ) PAMAM dendrimers have been synthesized. In the growth phase of dendrimers, two important building blocks, methyl acrylate for the half generation and EDA for the full generations, have been used. In order to improve the yield and decrease the time for the aminolysis step, a microwave-assisted technique was applied. Both of these dendrimers with different cores were grown up to 4.5 generations where surface modification, i.e. PEGylation, with 10% Poly(ethylene glycol )  bis(amine ) was performed. In order to increase the solubility of dendrimers, esteric surfaces were converted to carboxylic acid groups. Accordingly, the dendrimers were soluble in water or in water–methanol mixture which enabled their purification by liquid-phase polymer-based retention in each step. Finally, the resulting products that were characterized with (NMR and FTIR) spectroscopy were evaluated in vitro and in vivo . The analytical grade dendrimers were not cytotoxic to mouse fibroblasts and their biodistribution was mainly determined in the site of injection (peritoneum), liver and kidneys.